Strain softening and instability of sand under plane-strain conditions - Wanatowski, Dariusz (2008)
A comprehensive experimental study on the strain softening and instability behaviour of granular soil under plane-strain conditions is presented in this thesis. A new plane-strain apparatus was developed and used in this study. The study was carried out by conducting specialised plane-strain tests on a marine dredged sand. Based on several series of drained and undrained tests, the drained and undrained characteristics of the sand under plane-strain conditions were determined. It was shown that the critical state line under the plane-strain condition is different from that under the triaxial condition. The strain softening behaviour of sand was investigated using strain path testing method. Two types of strain softening, material softening and banding softening were identified.